Subalternitas Penganut Ahmadiyah dalam Novel Maryam Karya Okky Madasari - Kumaniren, Fabiola Agusta Wassy (Universitas Brawijaya, 2022)
The issuance of the Indonesian Ulema Council (Indonesia: Majelis Ulama Indonesia or MUI) fatwa declaring Ahmadiyya as a deviant sect and its followers as having departed from Islamic teachings has impacted the stereotypes surrounding the majority community. The novel